Behring Sea arbitration appendix to case of Her Majesty's government. - Behring Sea Tribunal of Arbitration.; United States.; Great Britain. ([S.l. : s.n., 1893)
The case, involving Great Britain and the United States, was heard before the Behring Sea Tribunal of Arbitration, in 1893. Mode of access: Internet.